Research on the Prospect and Path of Development of RMB as an International Reserve Currency - Guo, Wenhan (International Journal of Global Economics and Management, 2024)
Along with the global financial crisis and the weakening of the US dollar, the internationalization of the RMB has ushered in an important opportunity, and the promotion of the RMB as an international reserve currency not only promotes the internationalization of the RMB, but also has a great impact on China and even the world economy. At present, there are different views on the development prospect of RMB as an international reserve currency in China. This paper clarifies the development situation of RMB internationalization through in-depth investigation of the current development situation of RMB internationalization and the existing risk problems and puts forward the relevant development path to promote RMB as an international reserve currency on the basis of this. On this basis, it proposes a development path to promote the RMB to become an international reserve currency, which will provide thinking and reference for the RMB to realize internationalization from peripheralization to regionalization, and eventually become an international reserve currency